Frozen Histories or Narratives of Change? Contextualizing Land-Use Dynamics for Conservation of Historical Rural Landscapes - Dolejš, Martin; Nádvorník, Jiří; Raška, Pavel; Riezner, Jiří (Environmental management, 2019)
Current research has identified extensive changes in land-use structure and land management of Central European rural landscapes due to shifting political and economic trajectories. These changes are exemplified by diverse processes of agricultural intensification, privatization and land fragmentation, land abandonment and overall changes in modes of production. The extensive record of these historically specific processes has posed a fundamental challenge for rural landscape conservation, which is addressed in this paper. First, we identify the key contradictions in rural landscape conservation, which include (i) conservation based on cultural versus environmental/ecological values, (ii) conservation based on spatial landscape patterns versus individual landscape features, and (iii) conservation based on the preservation of past landscapes versus conservation that also address the processes of change. Subsequently, we use a case study of an existing open-air museum in Zubrnice, northern Czechia, to analyze and discuss these dichotomies. In this regional case study, we first contextualize the land-use/land-cover change (LULC) reconstructed from old maps using a thorough archive (documentary proxies) and field research (survey of agrarian terraces, clearance cairns, and remnants of orchards) that enabled the construction of a narrative of specific landscape structures and features. Finally, we integrate the collected data with a novel methodological approach that allow for the spatial identification of the landscape segments that represent the narratives of historical change in modes of rural production and are therefore suitable for integration within the existing open-air museum to improve its conservation and education status.
Keywords: Rural Population; Conservation of Natural Resources; ekosystém; lidé; zachování přírodních zdrojů; zemědělství; Ecology; ekologie; Ecosystem; venkovské obyvatelstvo; Humans; Agriculture